A Neutral Envelope‐Type Nanoparticle Containing pH‐Responsive and SS‐Cleavable Lipid‐Like Material as a Carrier for Plasmid DNA. Issue 8 (August 2013) - Akita, Hidetaka; Ishiba, Ryohei; Hatakeyama, Hiroto; Tanaka, Hiroki; Sato, Yusuke; Tange, Kota; Arai, Masaya; Kubo, Kazuhiro; Harashima, Hideyoshi
<x xml:space="preserve">Abstract</x> SS‐cleavable proton‐activated lipid‐like material (ssPalm) functions as a key element in a lipid nanoparticle in which pDNA is encapsulated. The ssPalm contains dual sensing motifs that can respond to the intracellular environment; a proton‐sponge unit (tertiary amines) that functions in response to an acidic environment (endosome/lysosome), and disulfide bonding that can be cleaved in a reducing environment (cytosol). <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>